Delivery of the Pseudomonas aeruginosa Phospholipase Effectors PldA and PldB in a VgrG- and H2-T6SS-Dependent Manner - Wettstadt, Sarah; Wood, Thomas E.; Fecht, Selina; Filloux, Alain (Frontiers in Microbiology, 2019)
The bacterial pathogen Pseudomonas aeruginosa uses three type VI secretion systems (T6SSs) to drive a multitude of effector proteins into eukaryotic or prokaryotic target cells. The T6SS is a supramolecular nanomachine, involving a set of 13 core proteins, which resembles the contractile tail of bacteriophages and whose tip is considered as a puncturing device helping to cross membranes. Effectors can attach directly to the T6SS spike which is composed of a VgrG (valine-glycine-rich proteins) trimer, of which P. aeruginosa produces several. We have previously shown that the master regulator RsmA controls the expression of all three T6SS gene clusters (H1-, H2- and H3-T6SS) and a range of remote vgrG and effector genes. We also demonstrated that specific interactions between VgrGs and various T6SS effectors are prerequisite for effector delivery in a process we called “à la carte delivery”. Here, we provide an in-depth description on how the two H2-T6SS-dependent effectors PldA and PldB are delivered via their cognate VgrGs, VgrG4b and VgrG5, respectively. We show that specific recognition of the VgrG C terminus is required and effector specificity can be swapped by exchanging these C-terminal domains. Importantly, we established that effector recognition by a cognate VgrG is not always sufficient to achieve successful secretion, but it is crucial to provide effector stability. This study is highlighting the complexity of effector adaptation to the T6SS nanomachine and shows how the VgrG tip can possibly be manipulated to achieve effector delivery.